2020
DOI: 10.1111/csp2.119
|View full text |Cite
|
Sign up to set email alerts
|

Revealing migration and reproductive habitat of invasive fish under an active population suppression program

Abstract: Endemic species face a variety of threats including predation from non‐native invaders. In some cases, however, invasive species can be managed by directly suppressing populations, and tracking technologies that allow researchers to identify movement patterns and aggregations representative of the population can facilitate suppression activities. In Yellowstone Lake (Yellowstone National Park, Wyoming), invasive lake trout (Salvelinus namaycush) have been the target of a population suppression program for over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 76 publications
0
11
1
Order By: Relevance
“…Lake Trout spawning activity across the species' range in North America typically increases during the evening, immediately after sunset (Martin and Olver 1980). However, during previous studies of broad-scale movement patterns of Lake Trout in Yellowstone Lake, there was no evidence of diel patterns in spawning behavior (Gutowsky et al 2020). Therefore, tracking surveys were conducted from 0600 to 1600 hours with boats traveling at a maximum speed of 9.7 km/h.…”
Section: Acoustic Trackingmentioning
confidence: 99%
“…Lake Trout spawning activity across the species' range in North America typically increases during the evening, immediately after sunset (Martin and Olver 1980). However, during previous studies of broad-scale movement patterns of Lake Trout in Yellowstone Lake, there was no evidence of diel patterns in spawning behavior (Gutowsky et al 2020). Therefore, tracking surveys were conducted from 0600 to 1600 hours with boats traveling at a maximum speed of 9.7 km/h.…”
Section: Acoustic Trackingmentioning
confidence: 99%
“…Passive and active tracking of acoustically telemetered Lake Trout have also been used to identify movement corridors to spawning locations and to target aggregations that are proximal or moving towards these grounds through a “Judas fish” technique (Gutowsky et al. 2020; Williams et al. 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In Yellowstone Lake, Lake Trout suppression has been conducted throughout the lake during the ice-free season but fall gillnetting effort has been heavily concentrated on known spawning locations, using larger mesh sizes to target spawning capable (>500 mm) females (Syslo et al 2011). Passive and active tracking of acoustically telemetered Lake Trout have also been used to identify movement corridors to spawning locations and to target aggregations that are proximal or moving towards these grounds through a "Judas fish" technique (Gutowsky et al 2020;Williams et al 2020). Based on assessment modeling results, annual exploitation levels of Lake Trout fully selected to suppression gill nets (≥4 years of age) has exceeded 50% since the mid-2010s (Syslo et al 2020).…”
Section: Lake Trout Reproduction In Yellowstone Lakementioning
confidence: 99%
See 1 more Smart Citation
“…Whereas RF models are unable to easily incorporate, RSF GLMMs can explicitly include individual ID as a random effect (Gillies et al, 2006). Further, generalized models can incorporate autocorrelation dependency structures (Zuur et al, 2017;Winton et al, 2018a;Griffin et al, 2019;Gutowsky et al, 2020), however, it is worth noting that defining the correct correlation structure still remains challenging within a use/availability (presences/pseudo-absences) sampling design (see Koper and Manseau, 2009;Fieberg et al, 2010). In this study, while BBMMs highlighted individual variation in space use, simplified GLMMs indicated including individual as a random effect contributed relatively less to explaining overall variance than the fixed effects alone.…”
Section: Benefits Challenges and Considerationsmentioning
confidence: 99%